An interprofessional training course in crises and human factors for perioperative teams. Issue 5 (2nd September 2016) - Stephens, Tim; Hunningher, Annie; Mills, Helen; Freeth, Della
ABSTRACT: Improving patient safety and the culture of care are health service priorities that coexist with financial pressures on organisations. Research suggests team training and better team processes can improve team culture, safety, performance, and clinical outcomes, yet opportunities for interprofessional learning remain scarce. Perioperative practitioners work in a high pressure, high-risk environment without the benefits of stable team membership: this limits opportunities and momentum for team-initiated collaborative improvements. This article describes an interprofessional course focused on crises and human factors which comprised a 1-day event and a multifaceted sustainment programme for perioperative practitioners, grouped by surgical specialty. Participants reported increased understanding and confidence to enact processes and behaviours that support patient safety, including: team behaviours (communication, coordination, cooperation and back-up, leadership, situational awareness); recognising different perspectives and expectations within the team; briefing and debriefing; after action review; and using specialty-specific incident reports to generate specialty-specific interprofessional improvement plans. Participants valued working with specialty colleagues away from normal work pressures. In the high-pressure arena of front-line healthcare delivery, improving patient safety and theatre efficiency can often be erroneously considered conflicting agendas. Interprofessional collaboration amongst staff participating in this initiative enabled general and specialty-specific interprofessional learning that transcended this conflict.